Reaction of Dental Pulp after Fracture of a Clinical Crown of Permanent Teeth - H. Hecová; V. Merglová; J. Stehlíková (Czech Dental Chamber, 2006)
Fractures of the tooth crown of permanent teeth belong to the most frequent dental injuries. The injury often affects hard dental tissues in complicated fractures, where the fracture line reached into dental pulp, affects dental pulp at well. The aim of this retrospective study was to analyze a group of patients, who were treated for a fracture of dental cap of permanent teeth at the Stomatological Clinic of the Faculty Hospital at Medical Faculty, Charles Unviersity in Plzen (Pilsen). The authors outline possible post-traumatic consequences of this kind of dental injury.